Investigation of Pile Behavior Toward Abutment Construction using PLAXIS 3D: Case Study on Lembak Bridge - Clinton Girsang; Paulus Pramono Rahardjo; Aswin Lim (Kadiri University, 2021)
Soil as a subgrade foundation under embankment construction often creates problems in terms of stability and settlement. Therefore, it needs improvement by using preloading embankment. This article presents the investigation of pile behavior towards two scenarios of abutment construction using Plaxis 3D, a three- dimensional finite element program. The use of two scenarios of analysis was Method A. The abutment construction phase conduct without using a preloading embankment, and Method B, where a preloading embankment constructs before the abutment construction. The case study location at the Lembak bridge. Compare the analysis results with the measured data. Results showed that Method A and Method B's pile deflection yielded four times and one point six times larger than the measure data, respectively. Hence, it indicates that Method B recommends for future construction of bridge abutment.